2016
DOI: 10.1001/jamadermatol.2015.3091
|View full text |Cite|
|
Sign up to set email alerts
|

Laboratory Monitoring During Isotretinoin Therapy for Acne

Abstract: IMPORTANCE Oral isotretinoin has been associated with several adverse effects, but evidence-based estimates of laboratory changes during isotretinoin therapy in large patient samples are limited. OBJECTIVE To develop estimates of the laboratory changes that occur during isotretinoin therapy for acne using extant data and meta-analytic methods. DATA SOURCES A comprehensive search strategy using Ovid/MEDLINE, EMBASE, and gray literature was conducted (1960-August 1, 2013) to identify all relevant studies of isot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
73
3
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 38 publications
(60 reference statements)
3
73
3
8
Order By: Relevance
“…Another serious complication is pancreatitis, which may be idiosyncratic, and thus not preventable or predictable, or due to elevated triglycerides. Elevated triglyceride levels are noted in practically all patients on isotretinoin, but may either not cross the threshold of abnormality or may be a marker of elevated arteriosclerosis risk rather than a cause . We agree with other authors that for the brief periods of therapy that are typical for acne, this is likely not relevant, except as a prognostic marker …”
supporting
confidence: 84%
See 1 more Smart Citation
“…Another serious complication is pancreatitis, which may be idiosyncratic, and thus not preventable or predictable, or due to elevated triglycerides. Elevated triglyceride levels are noted in practically all patients on isotretinoin, but may either not cross the threshold of abnormality or may be a marker of elevated arteriosclerosis risk rather than a cause . We agree with other authors that for the brief periods of therapy that are typical for acne, this is likely not relevant, except as a prognostic marker …”
supporting
confidence: 84%
“…The prevention of pancreatitis due to hypertriglyceridaemia is the primary reason for monitoring triglycerides in patients on isotretinoin. Recent reviews have looked at triglycerides in patients with acne and found that they are usually not highly elevated . However, it may still make sense to monitor patients extensively, if monitoring avoids an extremely rare catastrophic event.…”
Section: Discussionmentioning
confidence: 99%
“…One meta‐analysis was conducted in 1999 on isotretinoin effectiveness; however, this study considered single‐arm studies without comparators, did not evaluate treatment based on lesion counts, did not consider study quality or risk of bias and did not report adverse events. Systematic reviews have been published on isotretinoin adverse events such as psychiatric outcomes, laboratory abnormalities and inflammatory bowel disease; however, these were either not focused on randomized controlled trial evidence and thus are prone to confounding by indication, or did not concurrently consider the effect of isotretinoin. Therefore, given the prevalence of acne and broad use of isotretinoin, a review focusing on the highest quality of evidence on treatment efficacy and adverse events is well justified.…”
mentioning
confidence: 99%
“…Eine anonyme Umfrage an mehr als 2.300 Dermatologen während eines Kongresses bestätigte sehr große individuelle Unterschiede bei den Laborkontrollen [2]. Deshalb hat eine Autorengruppe um Kirby (Hershey, Pennsylvania) diese systematische Übersichtsarbeit mit der Frage nach Laborabweichungen von Triglyzeriden/Cholesterin sowie AST (= GOT) und ALT (= GPT) unter einer Isotretinointherapie erstellt [3]. …”
Section: Leukos Fett-und Leberwerte Im Blickunclassified